2023
DOI: 10.3389/fnut.2023.1123657
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary habits and the risk of migraine: a Mendelian randomization study

Abstract: ObjectiveThe important contribution of dietary triggers to migraine pathogenesis has been recognized. However, the potential causal roles of many dietary habits on the risk of migraine in the whole population are still under debate. The objective of this study was to determine the potential causal association between dietary habits and the risk of migraine (and its subtypes) development, as well as the possible mediator roles of migraine risk factors.MethodsBased on summary statistics from large-scale genome-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…The present study corroborates the conclusions of prior studies indicating a reverse correlation among physical activity, coffee consumption, cheese intake, BMI, and migraine [ 11 , 35 , 36 ]. However, this is the first study that employed MR to establish a causal relationship between these factors and migraine.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study corroborates the conclusions of prior studies indicating a reverse correlation among physical activity, coffee consumption, cheese intake, BMI, and migraine [ 11 , 35 , 36 ]. However, this is the first study that employed MR to establish a causal relationship between these factors and migraine.…”
Section: Discussionsupporting
confidence: 93%
“…Our results revealed that increased (genetically estimated) coffee consumption cheese intake, physical activity, and lower BMI were correlated with reduced risk of migraine in both the UKB and FinnGen cohorts, which is consistent with prior studies that have shown an inverse correlation between such factors and migraine [ 11 , 30 - 32 ]. The mechanisms causing these correlations are not fully understood; they may influence the risk of migraine by affecting brain function, inflammation, or other biological pathways.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A recent GWAS study of dietary habits based on the UK Biobank identified genetic associations between hundreds of dietary habits, providing the potential to study the causal relationship between dietary habits and disease risk 17 . Dietary habits have been widely used to assess causal relationships with diseases or traits, such as migraines 18 , osteoporosis 19 , and cerebral cortex structure 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol and coffee are triggering agents that are shown to have varying affects in different cultures on migraine attacks with both offending and protective aspects shown in studies [ 5 , 6 ]. Another Mendelian study revealed coffee, cheese, alcohol and white bread unrelated to migraine; whereas corn bread, cookies and poultry were found to be related to disease course [ 7 ]. Eating habits and consumed food are important in migraine in that they are modifiable pathogenetic factors.…”
Section: Introductionmentioning
confidence: 99%